Pengembangan Produk Merchandise dengan Teknologi Audio Visual sebagai Produk Unggulan Muatan Pendidikan Kampung Industri Tempe Sanan - Iriaji; Wening Patmi Rahayu; Purnomo; Eka Putri Surya; Alby Aruna; Surasak Jamnongsarn; Adinda Marcelliantika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Developing local creative industries through product innovation is an important strategy to increase the economic and educational value of communities. This research aims to develop merchandise based on audio visual technology as a means of education about the production process and uniqueness of tempeh in the Sanan Tempe Industrial Village. The research method involves collecting data through observation, interviews with industry players, and questionnaires to visitors. The product developed is in the form of an action figure as a mascot in the form of merchandise. The research results show that this merchandise is effective in increasing visitors' understanding of the tempe making process and increasing interest in educational tourism. Visitors become more interested and understand the ins and outs of tempeh production after interacting with this informative merchandise. Apart from that, this merchandise also helps promote Kampung Sanan as an attractive educational tourist destination. The conclusion of this research is that the integration of audio visual technology in merchandise can be used as an effective educational tool while increasing the attractiveness of local products. This innovative product not only functions as an educational tool but also as a promotional tool that can increase the economic value of local communities. This kind of innovation proves that a creative approach to product development can provide significant benefits to local communities.